2005
DOI: 10.1007/s10741-005-2346-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aldosterone and Mineralocorticoid Receptor Blockade on Vascular Inflammation

Abstract: Aldosterone, the final product of the renin-angiotensin-aldosterone system, is classically viewed as a regulator of renal sodium and potassium handling, blood volume, and blood pressure. Recent studies suggest that aldosterone can cause microvascular damage, vascular inflammation, oxidative stress and endothelial dysfunction. In animal models, aldosterone-mediated vascular injury in the brain, heart, and kidneys leads to stroke, myocardial injury, and proteinuria. These effects may be modified by dietary salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…Similar role is demonstrated for mineralcorticoid receptor (MR) [63]. Specifically, treatment with aldosterone and salt caused extensive inflammatory arterial lesions with perivascular macrophages in the rat heart and increased the expression of ICAM, cyclooxygenase-2, osteopontin, and MCP-1, effects that were decreased by MR blockade [63].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 74%
See 2 more Smart Citations
“…Similar role is demonstrated for mineralcorticoid receptor (MR) [63]. Specifically, treatment with aldosterone and salt caused extensive inflammatory arterial lesions with perivascular macrophages in the rat heart and increased the expression of ICAM, cyclooxygenase-2, osteopontin, and MCP-1, effects that were decreased by MR blockade [63].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 74%
“…Several studies have demonstrated that also aldosterone activation induces elevation of oxidative stress and vascular inflammation [63]. Similar role is demonstrated for mineralcorticoid receptor (MR) [63].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 82%
See 1 more Smart Citation
“…Hyperaldosteronism is associated with vascular inflammation (1,2,(8)(9)(10)(11)(12)(13)(14). Aldosterone infusion induces leukocyte infiltration into arteries of rats and increases the expression of proinflammatory markers (15,16).…”
mentioning
confidence: 99%
“…An interaction between inflammatory response and activation of neurohormonal systems was suggested [82,83]: animal studies and in vitro experiments have shown that angiotensin II (ATII) activates circulating leucocytes and promotes adhesion to the endothelium, which in response activates adhesion molecules, chemokines and inflammatory cytokines resulting in the production of reactive oxygen species (ROS) and induction of the transcription factor NF-B [84]. Similar observations have been made for aldosterone [85,86]. A series of experimental studies have demonstrated that inflammatory cytokines such as TNF , IL-1 and MCP-1 may directly contribute to the pathogenesis of CHF by inducing contractile dysfunction, ventricular dilation, cardiomyocyte hypertrophy, apoptosis and fibrosis [87][88][89].…”
Section: Inflammatory Factors: Cyclooxygenase-2 and Phosphorylated Akmentioning
confidence: 82%